A QUALITY CONTROL SYSTEM TO REDUCE UNCERTAINTY IN INTERPRETING FORMATION PRESSURES FOR RESERVOIR AND BASIN PRESSURE SYSTEM ANALYSIS. (26th March 2013) - Hortle, A.; Otto, C.; Underschultz, J.
<x xml:space="preserve">Abstract</x> Downhole formation pressure data can be difficult to obtain and the quality of the data produced varies significantly with age, tool type and geology. Furthermore, even if a new well is characterised effectively and high quality data obtained, the radius of investigation is small compared to the size of the area typically being assessed. Nevertheless, understanding the subsurface formation pressure system is a prerequisite for any basin or reservoir evaluation during exploration, appraisal and production. It requires integrating pressure and subsurface data from spatially disparate wells, and requires direct, quantitative comparison of historical and contemporary data‐sets. This comparison needs to be objective, repeatable and robust. This paper describes a qualitative system for systematically and objectively comparing all types of formation pressure measurements to provide a basis for a qualitative interpretation of the subsurface formation pressure system. The application of the system consists of a set of questions designed to assess the quality and quantity of formation pressure data available from information in the well completion report. Each question defines quantitative limits for key pressure test parameters that determine the quality class of the formation pressure of that test. The questions require a 'yes' or 'no' answer, and the cumulative set of answers results in a code that reflects the overall quality of the data. The resulting set of codes can be used directly or can be further subdivided into a set of five reliability classes. The system does not assess the accuracy of an individual pressure test, but provides a context for meaningful comparisons to be made of formation pressure data acquired under spatially and temporally disparate conditions. This allows for an interpretation of the data to be made that accounts for the variable reliability of individual data points. The system is generic and can be applied to any basin, onshore or offshore. It is suitable for field‐scale studies up to basin‐scale studies and can be applied to producing or non‐producing data. This paper outlines the underlying principles and the methodology required to apply the quality code system. It includes examples of how application of both the quality codes and the reliability classes can simplify the interpretation of a scattered data‐set and provide tools to effectively communicate the results.